Relaxin does not improve Angiotensin II-induced target-organ damage. - Nadine Haase; Julianna Rugor; Lukasz Przybyl; Fatimunnisa Qadri; Dominik N Müller; Ralf Dechend (PLoS ONE)
Relaxin is a corpus-luteum produced protein hormone with vasodilatatory, anti-fibrotic, and angiogenic properties that are opposite to angiotensin (Ang) II. We investigated whether or not relaxin ameliorates Ang II-induced target-organ damage. We used double transgenic rats harboring both human renin and angiotensinogen genes (dTGR) that develop severe hypertension, target-organ damage, and die untreated within 7-8 weeks. Recombinant relaxin at a low (26 μg/kg/d) and a high dose (240 μg/kg/d) was given to 4 week-old dTGR and age-matched Sprague-Dawley rats (SD). Systolic blood pressure increased progressively in untreated dTGRs from 162 ± 3 mmHg at week 5 to 225 ± 5 mmHg at week 7. Relaxin had no effect on blood pressure whereas SD rats were normotensive (106 ± 1 mmHg). Untreated and relaxin-treated dTGR had similarly severe cardiac hypertrophy indices. Relaxin did not ameliorate albuminuria and did not prevent matrix-protein deposition in the heart and kidney in dTGR. Finally, relaxin treatment did not reduce mortality. These data suggest that pharmacological doses of relaxin do not reverse severe effects of Ang II.